Sorption of La3+ cations by zeolites from aqueous solutions - Yu.V. Rekh; S.A. Bibanaeva; M.S. Valova; V.M. Skachkov; O.V. Fedorova; N.A. Sabirzyanov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
It is shown that the sorption of lanthanum cations by synthetic aluminosilicate zeolite, unlike natural ones, increases both in acidic and neutral conditions by 4 times (from 8 to 26%) and 8 times (from 4 to 33%), and the sorption capacity increases by 3-8 times to 145 and 184 mg/g, respectively. A comparative analysis of the applicability of the adsorption of Langmuir, Freundlich, Temkin, Dubinin-Radushkevich models to describe experimental isotherms of adsorption of lanthanum cations on synthetic zeolite is made. It is shown that the Langmuir model is best suited in aqueous media (R2 = 0,9996). This indicates that a homogeneous monolayer surface is formed as a result of sorption. Based on the pseudo-first, pseudo-second order models and the intraparticle diffusion model, an assumption is made about the ion-exchange nature of sorption. It has been shown that zeolites can almost quantitatively extract La3+ cations from aqueous solutions and are of interest as sorbents with a high sorption capacity.